Cycloaddition reactions of tetraaza macrocycle supported group 4 imido complexes and reversible addition of aryl isocyanate to a coordinated ureate ligand - Blake, A; Mountford, P; Nikonov, G; Swallow, D (1996)
The first tetraaza macrocycle supported zirconium imido complex [Zr(tmtaa)(NC 6H 3Pr i2-2,6)(py)] and the new titanium imido base-free analogues [Ti(tmtaa)(NAr)] (Ar = Ph or C 6H 4Me-4) react with isocyanates to give N,N′-bound ureate complexes; these can undergo exchange reactions with excess aryl isocyanate via reversible insertion into the Ti-N(ureate) bond; the X-ray structure of [Zr(tmtaa)- {(NC 2H 3Pr i2-2,6)(CO)(NBu t)}] is described (H 2tmtaa = tetramethyldibenzotetraaza[14]annulene).